MAHAR MUSAMMA DAN MAHAR MITSIL DALAM PELAKSANAAN PERKAWINAN - Muallim Hasibuan (AL-ILMU, 2023)
Among the good protections of Islam and its respect for women is that Islam gives them property rights. Because, in the period of ignorance, women became the party whose rights were oppressed and abused in their association. Islam wants to get rid of remnants of the ignorance system regarding women's affairs and their dowry. Mahar is a voluntary gift which is a symbol of a man's sincerity, honesty, and commitment in marrying a woman. Giving a dowry to a prospective wife is mandatory, marriage without mentioning the dowry "Tafwidh marriage" is legal, failure to mention the type and amount at the time of the marriage ceremony, does not cause the marriage to be cancelled. The scholars of the madhhab agree that dowry is not one of the pillars of the contract, but is one of the consequences of the existence of the contract. Therefore, the marriage contract may be carried out without mentioning the dowry. The scholars of the school of thought agree that there is no maximum amount in dowry, but they differ on the minimum limit. The dowry may be paid at the beginning (before intercourse) or at the end (after intercourse), as it can also be paid at the beginning of a part and at the end of another part. Dowry may be terminated under two conditions, let the time to be paid be known, and do not delay payment for too long. There are two types of dowry, musamma dowry and mitsil dowry. Mahar musamma is the dowry agreed upon by the bride and groom as stated in the editorial contract. While the mitsil dowry is the dowry that should be given to women that is usually accepted by other women who are equal to them, both in terms of age, beauty, wealth, mind, religion, virginity, widowhood, and country when the marriage contract is held. Keywords: Marriage, Dowry, Mazhab and Akad.